Making decisions: the normal interventions of Nissan 'mobility managers'. Issue 4 (4th July 2022) - Hind, Sam
ABSTRACT: In this article I investigate a decentralized infrastructure meant to assist autonomous vehicles in making decisions. More akin to a call centre than a centralized control room, Nissan's 'Seamless Autonomous Mobility' (SAM) project imagines that remote 'mobility managers' will intervene in the decision-making of autonomous vehicles, with the assistance of live video streams and other sensor data. Different from other kinds of AI microwork in which human workers prepare, imitate, or verify AI, mobility managers are envisioned instead as 'interveners', meant to directly and actively intervene in the movements of 'autonomous' vehicles when unable to negotiate an obstacle. Firstly, through a comparison between SAM and a traffic management system in Los Angeles, I argue that the former 'normalizes' intervention, in which decision-making delays become ordinary, if not altogether desirable. Secondly, through an analysis of a video in which such normalized interventions are imagined, I consider how SAM offers a kind of speculative mundanity in which remote workers, enabled by a technological infrastructure, embody a novel logic that modifies the social settings of driving.